Mieczysław Wolfke - a pioneer of holography - Petelczyc, Krzysztof (Photonics Letters of Poland, 2021)
Receiving the Nobel Prize in 1971 for the invention and development of the holographic method, Dennis Gabor mentioned Mieczysław Wolfke as the person who proposed this method as early as 1920 (which he did not know, independently making the same discovery). This article describes the history of Wolfke's pioneering work and tries to recreate the thought process that led to it - starting with the task of supplementing and verifying the diffraction grating theory proposed by Ernst Abbe, which he carried out as part of his doctorate at the University of Wrocław and habilitation at the University of Zurich and the Swiss Federal Institute of Technology in Zurich.. Full Text: PDF References W. Łaniecki, Kwartalnik Historii Nauki i Techniki, 21, 545-553 (1976). DirectLink W. Keesom, "Solidification of Helium", Nature 118, 81 (1926). CrossRef W. Keesom, M. Wolfke, "Two liquid states of helium", Konink. Akad. Wetensch. Amsterdam, Proc, 31(190b), 90-94 (1928). W. Keesom, Helium (Elsevier, Amsterdam 1942). E. Abbe, Die Lehre von der Bildentstehung im Mikroskop (F. Vieweg, Braunschweig 1910). CrossRef R. Torge, Postępy Fizyki, 53, 201-210 (2002). CrossRef A.Kiejna, Kwartalnik Historii Nauki i Techniki, 48, 7 (2003). DirectLink M. Wolfke, "Über die Abbildung eines Gitters bei künstlicher Begrenzung", Ann Phys. 339, 277 (1911). CrossRef M. Wolfke, Prace matematyczno-fizyczne, 22, 135 (1911). DirectLink M. Wolfke, "Über die Abbildung eines Gitters bei asymmetrischer Abblendung", Ann Phys. 342, 96 (1912). CrossRef M. Wolfke, "Über die Abbildung eines durchlässigen Gitters", Ann Phys. 342, 797 (1912). CrossRef M. Wolfke, "Zur Abbildung eines durchlässigen Gitters", Ann Phys. 343, 385 (1912). CrossRef K. Petelczyc, E. Kędzierska, Mieczysław Wolfke. Gdyby mi dali choć pół miliona… (OWPW, Warszawa 2018). DirectLink L.A. Aslanov, G.V. Fetisov, J.A.K. Howard, "Crystallographic Instrumentation", Oxford (1998). CrossRef M. Wolfke, Wiadomości matematyczne 17, 1 (1913). DirectLink M. Wolfke, "Allgemeine Abbildungstheorie selbstleuchtender und nicht selbstleuchtender Objekte", Ann Phys. 344, 569 (1912). CrossRef M. Wolfke, "Über die Abbildung eines Gitters außerhalb der Einstellebene", Ann Phys. 345, 194 (1913). CrossRef M. Wolfke, Verhandlungen der DPG, 15, 1123 (1913). M. Wolfke, Verhandlungen der DPG, 15, 1215 (1913). M. Wolfke, Verhandlungen der DPG, 16, 4 (1914). M. Wolfke, "Fragen zur Pathologie des menschlichen Oedems", Physikalische Zeitschrift, 22, 375 (1921). CrossRef Akta osobowe - Wolfke Mieczysław, Archiwum Akt Nowych sygn. 2/14/0/6/6638, Warszawa M. Wolfke, Physikalische Zeitschrift, 21, 495 (1920). DirectLink S. Lundqvist, Nobel Lectures, Physics 1971-1980 (World Scientific Publishing Co. Singapore 1992) CrossRef